Developing Fire Adapted Communities: The Importance of Interactions Among Elements of Local Context. Issue 10 (2nd October 2016) - Paveglio, Travis B.; Abrams, Jesse; Ellison, Autumn
ABSTRACT: Resident perceptions and actions related to wildfire management are influenced by a complex set of factors that are often tied to a specific local context. We conducted in-depth case studies in two diverse communities to better illustrate how elements of local social context collectively influence wildfire perspectives and behaviors in a given locality. Our results suggest that the influence of commonly cited predictors for wildfire mitigation actions, including homeowners' associations, vegetation preferences, and previous experience with wildfire, can vary based on their interaction with other elements of local context such as residents' desire for privacy, preferences for wildland or ornamental vegetation, identification as "suburbanites" or "country residents, " and willingness to collectively organize. We compare our results to existing wildfire social science findings and argue for a more holistic view of local social context as a way to design tailored strategies for increasing resident responsibility for wildfire.